Interactions between corticotropin releasing factor signaling and prophylactic antibiotics on measures of intestinal function in weaned and transported pigs - McConn, Betty R.; Kpodo, Kouassi R.; Rivier, Jean E.; Behan, Dominic P.; Richert, Brian T.; Radcliffe, John S.; Lay, Donald C.; Johnson, Jay S. (Frontiers in Physiology, 2023)
The study objective was to evaluate the interaction between corticotrophin releasing factor (CRF) receptor signaling and prophylactic antibiotic administration on intestinal physiology in newly weaned and transported pigs. Pigs (n = 56; 5.70 ± 1.05 kg) were weaned (20.49 ± 0.64 d), a blood sample was taken, and then pigs were given an intraperitoneal injection of saline (SAL; n = 28 pigs) or a CRF receptor antagonist (CRFA; n = 28 pigs; 30 µg/kg body weight; Astressin B), and then were transported in a livestock trailer for 12 h and 49 min. A second and third intraperitoneal injection was given at 4 h 42 min and 11 h 36 min into the transport process, respectively. Following transport, 4 SAL and 4 CRFA pigs were blood sampled and euthanized. The remaining 48 pigs were individually housed and given dietary antibiotics [AB; n = 12 SAL and 12 CRFA pigs; chlortetracycline (441 ppm) + tiamulin (38.6 ppm)] or no dietary antibiotics (NAB; n = 12 SAL and 12 CRFA pigs) for 14 d post-transport. Blood was collected at 12 h and on d 3, 7, and 14, and then pigs were euthanized on d 7 (n = 24) and d 14 (n = 24) post-weaning and transport. Circulating cortisol was reduced (P = 0.05) in CRFA pigs when compared to SAL pigs post-weaning and transport. On d 7, jejunal villus height and crypt depth was greater overall (P < 0.05) in AB-fed pigs versus NAB-fed pigs. On d 14, ileal crypt depth was reduced (P = 0.02) in CRFA pigs when compared to SAL pigs. Jejunal CRF mRNA abundance tended to be reduced (P = 0.09) on d 7 in CRFA pigs versus SAL pigs. On d 14, jejunal tumor necrosis factor-alpha was reduced (P = 0.01) in AB-fed pigs versus NAB-fed pigs. On d 7, change in glucose short-circuit current tended to be increased (P = 0.07) in CRFA pigs fed the AB diet when compared to CRFA pigs fed the NAB diet. In conclusion, CRFA pigs and pigs fed AB had some similar biological intestinal function measures post-weaning and transport.